Design And Build A Web-Based Asset Management Information System at Pt Thamrin Telekomunikasi Network - Effendy, Muhammad Yusuf; Nurninawati, Euis; Ari Setiyawan, Ahmad (Pandawan, 2022)
Asset management is a series of activities related to identify the assets needed, identify the need for funds, acquire assets, provide logistics and maintenance support systems for assets, delete or update assets so that the objectives are effectively and efficient. At PT Thamrin Telekomunikasi Network data collection for each IT asset companies in the form of laptops, servers, network devices and peripheral devices others are done manually using Microsoft Excel. But sometimes, IT staff forgot to update data such as data on the expiration of the asset warranty period and transfer of ownership of assets, as well as marking on assets still using stickers handwritten manually. Through this research, the author aims to designing and implementing a management information systemweb-based IT assets at PT Thamrin Telekomunikasi Network. Which method used in this study include interviews, observations and studies References. The analytical method used is the PIECES method and the design method The system created is described by the UML (Unified Modeling) method Language), for application development will use the SDLC method with the Xtreme Programming model, as well as the application testing method, namely the Black Box. The final result of this research is an IT asset management system web-based programming language built with HTML and Javascript, with MariaDB as the DBMS and using Laravel and Bootstrap as a framework of PHP and CSS. It is hoped that with this application, IT asset management process at PT Thamrin Telekomunikasi Network can be run more effectively, organized and more efficiently.